1995
DOI: 10.1128/jcm.33.2.505-507.1995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Paracoccidioides brasiliensis isolates by random amplified polymorphic DNA analysis

Abstract: We initially used 25 different random primers in order to test their ability to generate random amplified polymorphic DNA fragments from the dimorphic human pathogenic fungus Paracoccidioides brasiliensis. From the tested primers we chose five to distinguish between seven isolates of this microorganism. The DNA amplification patterns allowed clear differentiation of the seven isolates into two distinct groups with only 35% genomic identity. One of these groups contained two subgroups with 81% genetic similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 18 publications
2
20
0
2
Order By: Relevance
“…This difference in DNA and protein polymorphism was previously verified in other pathogenic fungi, such as Histoplasma capsulatum 23 and P. brasiliensis. 24,25 Therefore, the results of this study, connected with previous results from our group, 22 are in accordance with other fungal models.…”
Section: Discussionsupporting
confidence: 92%
“…This difference in DNA and protein polymorphism was previously verified in other pathogenic fungi, such as Histoplasma capsulatum 23 and P. brasiliensis. 24,25 Therefore, the results of this study, connected with previous results from our group, 22 are in accordance with other fungal models.…”
Section: Discussionsupporting
confidence: 92%
“…Genetic polymorphism in P. brasiliensis has been detected in the past by RAPD analysis (6,32,37) and chromosome analyses (8,21). It is also known that individual isolates show different degrees of pathogenicity in susceptible inbred mice (15,33,35).…”
Section: Discussionmentioning
confidence: 99%
“…However, the interaction of A. castellanii with T16B1 revealed that this strain was more efficient in surviving and killing the amoebae. Given that the armadillo strain was isolated about 7 years ago whereas Pb18 and Pb01 were isolated about 90 and 30 years ago, respectively [40, 41], these results point to the attenuation of Paracoccidioides spp. after prolonged in vitro subculturing.…”
Section: Discussionmentioning
confidence: 99%